Metaphors in Promotional Discourse of Indonesian Tourism: Ecological Discourse Analysis - Isti’anah, Arina; Suhandano; Winarti, Daru (Jordan Journal of Modern Languages & Literatures, 2025)
By incorporating larger datasets on tourism promotion, this paper aims to 1) identify metaphors used to promote Indonesian nature and 2) discuss the promotion frames ecologically based on the metaphors used. The data acquired from the Indonesia Travel website were uploaded and analysed using Sketch Engine and WMatrix5, with the conceptual metaphor theory (CMT) of Lakoff and Johnson (1980, 2003) applied within the ecolinguistics framework proposed by Stibbe (2015).). The analysis revealed that metaphor-related words were found in collocational and non-collocational relations in the form of adjectives, nouns, verbs, compound adjectives, and compound nouns to promote Indonesian topography, national parks, non-human species, and nature-based activities. The examined metaphors frame Indonesian nature as THE HOME OF COLOURFUL, UNUSUAL GEMS. However, the dominance of ’prosperity’ and ’purity’ as selling points articulates human stewardship of the ecosystem. The paradoxes of familiarity and attractiveness identified through metaphors express an eco-ambivalent discourse. Indonesia’s natural wealth, conceptualised as a ’treasure’, perpetuates a colonialist agency that stewards nature. Future research could look into how English metaphors are translated into Indonesian in tourism promotion discourse. The research can then determine whether the Indonesian metaphors produce a more beneficial discourse for the readers. Keywords: Corpus, Ecolinguistics, Fame, Ideology, Promotion. Highlights: Metaphors are a productive linguistic device to promote Indonesian tourism, mainly when promoting topography and national parks; Metaphors in Indonesian tourism are syntactically realized in both simple and complex structures, which can be identified through collocation and concordance analysis; The semantic domains of metaphor vehicles are found in the COLOUR, RESIDENCE, NATURAL PRECIOUS ELEMENTS, JUDGMENT OF APPEARANCE, RELIGION, and GIVING. The domains are assisted by Wmatrix 5; The metaphorical semantic domains generally project Indonesia as a HOME TO UNUSUAL COLORFUL gems; and Metaphors in Indonesian tourism are employed to promote the country’s purity, prosperity, and remoteness.